2015
DOI: 10.1177/1758573215571010
|View full text |Cite
|
Sign up to set email alerts
|

Current UK practices in the management of subacromial impingement

Abstract: Background: Controversy presently exists surrounding the management of patients with subacromial impingement. This study aims to highlight current UK practices in the management of these patients. Methods: BESS members were invited to complete a questionnaire and responses were received from 157 consultant shoulder surgeons. Results: Physiotherapy is an integral part of management for 93% of surgeons with a minimum period of 12 weeks being most popular prior to consideration of arthroscopic subacromial decompr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
(26 reference statements)
4
5
0
Order By: Relevance
“…This may in part be due to mass emails such as this survey being treated as spam by NHS servers and therefore not reaching the intended recipients. The response rate is, however, in accordance with other published BESS surveys [14]. Of concern is that some surgeons are offering treatments which may potentially cause harm in the medium and longer term, and there appears to be a poor understanding of the literature in terms of risk factors for recurrence of tear in this category of patient.…”
Section: Willingness To Participate In a Multi-center Trialsupporting
confidence: 78%
See 1 more Smart Citation
“…This may in part be due to mass emails such as this survey being treated as spam by NHS servers and therefore not reaching the intended recipients. The response rate is, however, in accordance with other published BESS surveys [14]. Of concern is that some surgeons are offering treatments which may potentially cause harm in the medium and longer term, and there appears to be a poor understanding of the literature in terms of risk factors for recurrence of tear in this category of patient.…”
Section: Willingness To Participate In a Multi-center Trialsupporting
confidence: 78%
“…134 complete questionnaires were received (28.5% of the total 470 surgeons surveyed), a comparable response rate to previously published BESS surveys [13][14][15]. Free text comments indicated that whilst some surgeons had rejected patch repair after attempting the procedure in the past, others appeared to be interested in considering this treatment in the future.…”
Section: Resultsmentioning
confidence: 69%
“…Subsequent to the first two reported studies in the 1950s conducted by Hollander et al 15 and Wrenn et al 16 , on the effects and benefits of corticosteroids in management of intra-articular and soft tissues conditions respectively, their use in injectable forms has gained universal acceptance. 17 The majority of shoulder surgeons use corticosteroid injections as an integral part of their clinical management for patients presenting to them with shoulder pain, 18 and recent national commissioning guidelines . Mean visual analogue scale (VAS) scores for patients who were managed conservatively and discharged successfully by 6 months (blue, circle), patients who were listed for/ had surgery by 6 months for on-going symptoms (green, diamond) and patients whose symptoms became overtly suggestive of cervical spinal pathology (red, square).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of shoulder surgeons use corticosteroid injections as an integral part of their clinical management for patients presenting to them with shoulder pain, 18 and recent national commissioning guidelines for subacromial impingement and rotator cuff tendonopathy recommend their use in primary care. 6…”
Section: Discussionmentioning
confidence: 99%
“…The initial management of SAS includes rest or activity modification and shoulder exercises (3,4). Local injections and physiotherapy may also aid in healing of the patients (3,(5)(6)(7)(8). Although the pharmacologic mechanism of action is not similar, both corticosteroids and local anesthetics produce similar effects with regard to pain and subsequent improvement in strength and upper limb function (9).…”
Section: Introductionmentioning
confidence: 99%